Ability of different microalgae species in synthetic high‐strength wastewater treatment and potential lipid production. Issue 11 (23rd February 2016) - Zhao, Yongjun; Ge, Zhigang; Lui, Hui; Sun, Shiqing
Abstract: BACKGROUND: Three green microalgae ( Selenastrum capricornutum, Scenedesmus obliquus, and Chlorella vulgaris ) were evaluated for their capability to support nutrient removal and to accumulate lipids in their cell during a 14‐day treatment of synthetic high‐strength wastewater (i.e. high carbon [C] and high nitrogen [N] loading wastewater) in batch tests. RESULTS: Scenedesmus obliquus was superior to the other microalgae. It reached a removal rate of up to 82.49% ± 2.20% chemical oxygen demand (COD), 61.18% ± 2.11% total nitrogen (TN), and 95.40% ± 1.83% total phosphorus (TP) for high C loading wastewater and 80.04% ± 2.17% COD, 60.05% ± 2.20% TN, and 96.87% ± 1.95% TP for high N loading wastewater. However, the highest lipid productivity of microalgae was determined in C. vulgaris with 132.06 mg L −1 and 36.37 mg L −1 for high C and high N loading wastewater, respectively, because of its biomass production and relatively higher lipid content. CONCLUSION: The appropriate screen of microalgal species is crucial to achieve optimal nutrient removal and high lipid productivity in synthetic high‐strength wastewater treatment, and S. obliquus is the optimal species. © 2016 Society of Chemical Industry